The fourth amendment and the potential use of field-portable mass spectrometry systems in law enforcement - Gizzi, Michael C. (Journal of crime and justice, 2019)
The advent of new technology presents new opportunities for forwarding thinking law enforcement administrators and new legal challenges for the courts. One such new technology is portable mass spectrometry. Such devices are very powerful analytical tools that can be used in the field to identify a wide range of contraband and other dangerous materials, including illegal drugs, explosive residue, and toxic substances. This paper examines the potential uses of portable mass spectrometry devices by law enforcement and presents analysis of the legal challenges that its use would present. Because criminal justice practice and legal analysis often lags behind the development and use of new technologies, comparison to current methods for detecting contraband is useful. In the case of portable mass spectrometry, the closest comparison would be the use of narcotics detection canine sniffs. Case law concerning dog sniffs is examined and predictions regarding the application of those legal guidelines to the use of portable mass spectrometry are made.